Singapore in Global History - Heng, Derek; Aljunied, Syed Muhd Khairudin (ICAS Publications Series, 2011)
This important overview explores the connections between Singapore's past with historical developments worldwide until present day. The contributors analyse Singapore as a city-state seeking to provide an interdisciplinary perspective to the study of the global dimensions contributing to Singapore's growth. The book's global perspective demonstrates that many of the discussions of Singapore as a city-state have relevance and implications beyond Singapore to include Southeast Asia and the world. This vital volume should not be missed by economists, as well as those interested in imperial history, business history and networks. This title is available in the OAPEN Library - http://www.oapen.org.